Criteria determining school choice among the ethnic minority high school students - Tódor, Imre (Central European Journal of Educational Research, 2020)
In our paper we sought for the answer to the question: based on which motives do students from various types of high schools (in our case, denominational or non- denominational school) make their choice of educational institution? The target group of our research consists of the 9th and 11th grade students of Harghita County’s denominational (Roman Catholic, Reformed, Unitarian) schools and the non-denominational ones added to them. All in all, eight high schools got into our sample. We conducted a survey by questionnaire, the sample including 1,064 people. We analyzed the decision criteria formed based on motives behind the decision (primary and secondary effects) on the one hand, and followed the decision making process on the other. The non-denominational sector is often chosen by the elite- and institution-oriented student group, who has great expectations of the institution, e.g. - top of the line standards of education, outstanding achievement indicators, prestige of the institution, local reputation. According to the clusters created from the motives, the value- and community-oriented student group, as well as the one following the orientation of the peer group, can be found in significantly higher proportion in denominational schools.